Probabilistic analysis of the evolution of degradation of natural stone claddings applying Markov chains - Silva, A.; De Brito, J.; Gaspar, P. L.; Neves, L. C. (Revista ALCONPAT, 2015)
The service life prediction models intend to extrapolate the future behaviour of building elements,anticipating the instant at which an intervention is required. Markov chains can be used to assess thefuture condition of the construction components and are applied in this study to model the service lifeof stone claddings (directly adhered to the substrate), based on visual inspections of buildings in serviceconditions. The degradation of stone claddings is evaluated using a discrete scale with five conditionlevels. In this study the probability of transition from degradation conditions and the time spent in eachof these conditions are evaluated. This study also allows a better understanding of the influence of theexposure conditions on the evolution of degradation of the claddings under analysis.Keywords: Markov chains; service life prediction; stone claddings.